Radical Prostatectomy is a Valuable Treatment Alternative in Patients with High-Risk Prostate Cancer - TİNAY, İLKER; TANIDIR, YILÖREN (GALENOS YAYINCILIK, 2015)
Objective To review the high-risk prostate cancer (PCa) patient database with special emphasis on the role of radical prostatectomy (RP) in comparison to external beam radiotherapy (EBRT). Materials and Methods A total of 102 patients with complete and long-term follow-up data were included. High-risk PCa was defined as: a pre-treatment PSA level of >= 20 ng/mL and/or a primary Gleason score of >= 4 and/or clinical stage >= T3N0M0 disease. A total of 45 (42.5%) patients underwent radical RP with extended pelvic lymphadenectomy for-high risk PCa and a total of 57 (53.8%) patients received EBRT. Results The mean overall survival (mean survival 95.2 vs. 129.2 months, log rank p=0.73) and cancer-specific survival (mean survival 104 vs. 151.4 months, log rank p=0.35) were not significantly different between RP and EBRT groups. Univariate analysis of variables that may affect overall survival showed no significant effect of pre-treatment PSA, Gleason score, clinical stage or type of therapy. The only factor which reached statistical significance was patient age (p=0.002). Multivariate analysis of variables also showed no significant effect of pre-treatment PSA, Gleason score, clinical stage or type of therapy and, again, the only factor which reached statistical significance was patient age (p=0.012). Conclusion Radical prostatectomy appears to be an effective and a non-inferior treatment option in patients with high-risk localized PCa with acceptable overall and cancer-specific survival compared to RT. Therefore, as the guidelines suggest, it should be provided as an option during patient consultation for a proper informed decision-making.
Keywords: High-risk prostate cancer; radical prostatectomy; radiotherapy; hormonal therapy